2021
DOI: 10.1007/s13178-021-00627-1
|View full text |Cite
|
Sign up to set email alerts
|

Why Report? Sex Workers who Use NUM Opt out of Sharing Victimisation with Police

Abstract: Background National Ugly Mugs (NUM) is a UK-wide violence prevention and victim support charity that provides a mechanism for sex workers to share safety information and obtain support for harms that they may experience during the course of their work. Over the past several years, NUM has witnessed a decline in sex workers willing to access police as part of their recovery journeys after experiencing victimisation. In 2012, 28% of those reporting to NUM chose to engage with the legal system; in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We will be consulting with sex workers about hate crime as it is on our report form and we suggested this in our submission to the Law Commission that conducted a consultation on hate crime laws in 2020. 68 For scholarship which has a participatory and collaborative ethos and practice, there is an urgent need for research that is led by community consultation as there has been in so many communities that routinely experience hate crime. 69 These realities are debates below in relation to what the hate crime literature says on the usefulness of the concept.…”
Section: • Crown Prosecution Service Engagementmentioning
confidence: 99%
“…We will be consulting with sex workers about hate crime as it is on our report form and we suggested this in our submission to the Law Commission that conducted a consultation on hate crime laws in 2020. 68 For scholarship which has a participatory and collaborative ethos and practice, there is an urgent need for research that is led by community consultation as there has been in so many communities that routinely experience hate crime. 69 These realities are debates below in relation to what the hate crime literature says on the usefulness of the concept.…”
Section: • Crown Prosecution Service Engagementmentioning
confidence: 99%
“…For any hate crime policy to work, it would require police officers (and others working in the criminal justice system) to put their assumptions about sex workers to one side and recognise agency in their involvement with the industry, their boundaries and ability to engage in and withdraw consent. Research has found that even those sex workers who had positive experiences with the police did not expect respectful treatment (Klambauer, 2018) and there is vast evidence that the police perpetuate violence and stigma, codify gender norms, and stereotype sex workers based off media representations (Klambauer, 2019;Bowen et al, 2021;ICRSE, 2020).…”
Section: Peer-reviewed Articlementioning
confidence: 99%
“…Repeat victimisation is common, as is significant under-reporting of crimes to the police [8][9][10][11]. Even when cases do get reported, sex workers often experience discrimination [12,13] and mixed responses from police officers [14].…”
Section: Introductionmentioning
confidence: 99%